Status of Subfamily Poritiinae (Lycaenidae) in Indian Himalayas with Taxonomic Notes on Type-species, Poritia hewitsoni Moore - Kumar, Charn; Sidhu, Avtar Kaur; Rose, H. S. (Indian Forester, 2011)
The subfamily Poritiinae Doherty is represented by four species referable to two genera from India viz., Phama geta Fawcett, Hewitsoni hewitsoni Moore, Ercinoides trishna Fruhstorfer (of genus Poritia Moore) and Phalena harterti Doherty (of genus Simiskina Distant). In present studies despite repeated surveys in Indian Himalayas only one female of Poritia hewitsoni could be collected, which infers that this family is under threat in this region. The female genitalia of the type-species Poritia hewitsoni has been studied for the first time and accordingly the subfamily and generic diagnosis have been updated by incorporating these characters.